High incidence of undiagnosed deep vein thrombosis among hospitalized people living with HIV: a cross-sectional study - Robert Bizaleri Baluku; Faith Ameda; Eva Nabawanuka; Christine Sekaggya-Wiltshire (Thrombosis Journal)
Abstract Background Deep venous thrombosis (DVT) is part of a spectrum of venous thromboembolism, which also includes pulmonary embolism. Up to 50% of hospitalized individuals who develop pulmonary embolism have DVT. Pulmonary embolism is responsible for up to 10% of hospital deaths. However, the burden and specific risk factors for DVT among inpatients living with HIV in our setting are not well established. Thromboprophylaxis, which reduces the risk of DVT, is not routinely administered to all inpatients. Understanding the burden and risk factors for DVT in this population can guide the implementation of preventive measures, identify high-risk individuals, and inform guidelines for thromboprophylaxis. Methods This cross-sectional study was conducted between October 2023 and April 2024 in two National Referral hospitals among hospitalized people living with HIV. A total of 186 participants were consecutively sampled and enrolled in the study. All adult inpatients living with HIV who fulfilled the eligibility criteria had a bedside Doppler ultrasound scan of the lower limbs for DVT. Relevant demographic, clinical, laboratory, and HIV-related data were obtained. Both bivariable and multivariable analyses were performed via R software. Results Up to 186 participants were enrolled, with a median age of 40 years (interquartile range (IQR): 34–52). The prevalence of lower limb DVT was 18.3% (34/186). The participants with DVT had a median age of 49 years (IQR: 39–56, p-value 0.045). Up to 53% (99/186) of the participants were male. The median duration of hospitalization was 5.0 days (IQR: 4.0–7.8) among those with DVT. A positive history of cigarette smoking was identified in 6.5% (12/34) of the participants and was significantly associated with the development of DVT (P-value = 0.004). TB coinfection was significantly associated with DVT, with a prevalence ratio (PR) of 2.22 (P-value = 0.007). A low CD4 (< 200) was also significantly associated with lower limb DVT (PR = 2.70, P-value = 0.003). Conclusion The prevalence of lower limb DVT among hospitalized people living with HIV is high (18.3%) in our setting. Older age, a positive history of smoking, a low CD4 count (< 200), and TB coinfection are significant risk factors for DVT in HIV-positive inpatients.